Effect of salt stress on photosynthesis and related physiological characteristics of Lycium ruthenicum Murr - Jun Luo; Cui hua Huang; Fei Peng; Xian Xue; Tao Wang (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2017)
Halophytes could withstand the hyper-salinity soil and survive widely in areas where soil salt content is high because they can endure salt stress to a certain extent. Lycium ruthenicum Murr (LRM), with significant nutritional and medicinal values, is one of the most important native halophytes in the arid oasis-desert transition zone of northwestern China. In recent years, artificially planting LRM has been being popular since it can improve saline-alkalized soil and increase the income of local farmers as well. More efforts about the artificial planting of LRM are put in enhancing the productivity and quality, but survivorship of LRM seedling by appropriate saline irrigation is still unclear in arid areas. A field experiment was conducted to explore the responses of LRM to four levels of saline water irrigation (Ec of irrigation water: 2.00 μs cm−1 (T1), 4.51 μs cm−1 (T2), 6.89 μs cm−1 (T3), and 9.00 μs cm−1 (T4)) during the growing seasons in 2014 and 2015. The average soil electrical conductivity (Eca) in 0–60 cm depth increased while the biomass of LRM decreased with increasing Ec of irrigation water, and the differences of Eca among treatments decreased with increasing salinity level. In contrast to previous research findings, salt stress had more significant effect on photosynthesis and chlorophyll fluorescence of LRM, in which great changes were caused by a threshold following the increased salinity. Most of the light energy absorbed by LRM was used for photosynthesis and heat dissipation when soil salinity was low, what was used for chlorophyll fluorescence when soil salinity was high. The results of the experiment indicate that T2 was the most suitable irrigation method for artificially planting LRM in the field, and it’s the key to save freshwater resources in arid areas and improve the production of saline-alkali land.